Effects of plain water intake before bedtime on sleep and depressive mood among middle-aged Japanese men - Kosuke Kaida; Kazane Itoi; Yoshiharu Soeta; Toshihiko Ooie; Katsutaka Oishi (PLoS ONE, 2026)
Although adequate water intake during the day enhances mental health, its effects during sleep remain unknown. We aimed to define the impact of plain water intake before bedtime on sleep parameters and depressive mood. We surveyed 2,000 Japanese using a questionnaire to determine associations between pre-bedtime water intake and depressive mood measured using the Center for Epidemiologic Studies Depression Scale (CES-D; Study 1). We also compared the effects of consuming 280 mL of plain water immediately before bedtime and of not consuming any beverages for at least 2 hours before bedtime (Study 2). The findings of Study 2 indicated that plain water intake immediately before bedtime decreased depressive mood in the morning, prolonged REM sleep latency, and reduced the duration of REM sleep. However, plain water intake also increased the likelihood of nocturia. Although balancing advantages and disadvantages is essential, the practice of consuming plain water before bedtime is a simple and effective way to enhance subjective wellbeing.